A study on the heat affected zone and machining characteristics of difficult-to-cut materials in laser and induction assisted machining. (September 2020) - Kim, Jun-Hwan; Kim, Eun-Jung; Lee, Choon-Man
Abstract: Difficult-to-cut materials are increasingly used to produce products in high-tech automobile, aerospace and other industries. The difficult-to-cut material is excellent in mechanical properties so that conventional machining is difficult. Thermally assisted machining (TAM) is an effective method of machining these difficult-to-cut materials. In TAM, a heat source proceeds the machining tool, which locally preheats and softens the workpiece. Laser assisted machining (LAM) is a typical TAM machining method. While the laser heat source is an excellent preheating method because it directly irradiates the material, it is expensive and the workpiece temperature drops rapidly. Therefore, in recent years, TAM studies using various heat sources other than lasers, such as induction assisted machining (IAM) and plasma assisted machining (PAM) have been carried out. The induction heat source preheats the material using high-frequency current. The laser heat source and induction heat source differ in their preheating method, which has an effect on the heat affected zone and the machining area. In this study, changes in the heat affected zone related to the feed rate of laser and induction heat sources was confirmed. The heat affected zone, preheating temperature and depth of cut of Inconel 718 and Ti-6Al-4 V were investigated through thermal analysis and preheating experiments. In addition, LAM and IAM were performed to compare the machining characteristics such as cutting force and surface roughness according to the feed rate and to verify the effect of improving the machining characteristic.